Contextual Coordination between Objects - Buffo, Mathieu; Buchs, Didier (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de Software, 1996)
Notwithstanding the promises it provides for the future of software engineering, the object paradigm suffers from a lack of development methods focusing on the coordination between objects. The distinction of coordination and computation mechanisms is an important separation principle for increasing the management and understanding of the interactions among objects and the configurations of objects on the target systems. This paper shows that contextual coordination must be introduced during the object oriented analysis in order to early take into account the inevitable constraints of the concrete implementation. This contextual coordination leads to a hierarchical model composed of imbricated execution contexts of objects.